Japanese enterprises in ASEAN countries : statistical outlook - Katano, Hikoji (Kobe : Research Institute for Economics & Business Administration, Kobe University, 1981)
The book examines Japans industrialization and foreign direct investment in the ASEAN countries.
Includes bibliographical references.
lje 17/01/2019
Loans
Keywords: Investments, Foreign; Corporations---Japanese--Finance; Japan; Southeast Asia